An Exploration of Nurses’ Experience of Family Presence During Resuscitation in Intensive Care Setting - Ni Putu Wahyu Ariani; Yanny Trisyani; Titin Mulyati (Faculty of Nursing Universitas Padjadjaran, 2021)
The family presence during resuscitation (FPDR) has received wide support to be implemented in the ICU.The implementation of FPDR has positive impacts on family satisfaction. However, some of the nurses’ opinion still not agree on implementation of FPDR in ICU. This research therefore utilized phenomenological approach to gain descriptive explanation regarding this phenomenon. The purpose of this study is to explore the nurse’s experiences in the implementation of FPDR in the ICU. This research was conducted on the year 2020 and qualitative phenomenological approach was utilized for this research. Ten (10) ICU nurses have participated in this study and in-depth interview was employed for data collection. Data analysis is conducted using Colaizzi. Result of this research areexplained in 6 themes which describe the phenomenon of nurses’ experience onfamily presence during recusitation, as follows: (1) Decisions on family; (2) From burdened to selfconfident; (3) Families enhancing teamwork; (4) The bereaved family disrupts the CPR process; (5) Feels of ignoring patiets’ family and (6) Expectingthe family be accompanied by staff nurse.From a nurse’s perspective, the implementation of FDPR has a positive impact on patients, families and on the ICU nurse team. However, this also has an unpleasant impact on ICU nurses, especially if the nurse is not ready for the practice. Therefore, policy support and training for nurses are needed in its implementation.